Editorial (english) - Moosburger, Laura B.; Candido, Gisele Batista (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2023)
More than a subject of philosophical reflection, affection has almost always been present in philosophy as constitutive of the very principle of philosophy, this edition has the dossier "The Affects in Philosophy and the Philosophical Dimension of Affects". And, this number of Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics is also composed of works originating from the continuous flow of this journal